MANAGEMENT OF FACILITIES AND INFRASTRUCTURE AT SMP IT AL-IKHWAN TANJUNG MORAWA - Syahrin, Muhammad Alfi; Fadhli, Muhammad; Syukri, Makmur (Pena Cendekia Insani, 2025)
Students are the most important assets for every country in This study aims to describe and analyze the management of facilities and infrastructure at SMP IT Al-Ikhwan Tanjung Morawa. The focus of the study covers five main aspects, namely planning, procurement, inventory, utilization and maintenance, and disposal of educational facilities and infrastructure. This study is motivated by the importance of the availability and management of adequate facilities to support the effectiveness of the learning process. The research approach used is qualitative with a case study method. Data were collected through in-depth interviews, observations, and documentation, then analyzed descriptively. The results of the study indicate that the management of facilities and infrastructure at SMP IT Al-Ikhwan Tanjung Morawa has been carried out systematically, but there are still obstacles in terms of the suitability between planning and realization, budget limitations, and suboptimal maintenance. Some educational facilities do not meet national education standards, especially in terms of information technology and comfort of learning spaces. These findings indicate the need to strengthen the management of facilities and infrastructure in a sustainable manner by involving all stakeholders, including the principal, teachers, administrative staff, and school committees. This study provides theoretical and practical contributions in the development of educational policies, especially in the aspect of effective and efficient facility management in Islamic-based private school environments.